1998
DOI: 10.1021/jo971688+
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Synthesis of Benzopiperazinones

Abstract: This article describes an efficient method for the solid phase synthesis of benzopiperazinones (1,2,3,4tetrahydroquinoxalin-2-ones) with four independently variable functional groups. Commercially available 4-fluoro-3-nitrobenzoic acid (FNBA) was anchored directly to Wang resin and to amino acid-containing Wang resin. Treatment of these resins with amino acid derivatives afforded enantiomerically pure aniline intermediates via an ipso-fluoro displacement in high yields. Reduction of the aromatic nitro group wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 13 publications
1
59
0
Order By: Relevance
“…The choice of these scaffolds for the attachment of HN pharmacophoric elements was based on several criteria. The benzimidazole and o-phenylenediamine scaffolds were first selected on the basis of previous reports that indicated that these types of molecules could be used as effective nontoxic peptide mimics and/or activators of specific membrane receptors (Kubo et al, 1993;Khan et al, 1996;Morales et al, 1998;Zarrinmayeh et al, 1999;Wu and Ede, 2001;Balboni et al, 2002;Heitsch, 2002). The next criteria was based on the principle that these molecules contain sites on which guanidino and phenolic hydroxy groups can be attached and still conserve enough freedom for proper orientation and interaction with the HN receptor(s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of these scaffolds for the attachment of HN pharmacophoric elements was based on several criteria. The benzimidazole and o-phenylenediamine scaffolds were first selected on the basis of previous reports that indicated that these types of molecules could be used as effective nontoxic peptide mimics and/or activators of specific membrane receptors (Kubo et al, 1993;Khan et al, 1996;Morales et al, 1998;Zarrinmayeh et al, 1999;Wu and Ede, 2001;Balboni et al, 2002;Heitsch, 2002). The next criteria was based on the principle that these molecules contain sites on which guanidino and phenolic hydroxy groups can be attached and still conserve enough freedom for proper orientation and interaction with the HN receptor(s).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the less rigid molecule of o-phenylenediamine, which possesses a hydrophilic skeleton, can also be used as a linker of pharmacophoric elements via attachment on adjacent free amino groups. Ortho-phenylenediamine has been successfully used as a precursor for the synthesis of tetrahydroquinoxaline-2-ones (Lee et al, 1997), benzopiperazinones (Morales et al, 1998), benzimidazoles, and quinoxalines (Wu and Ede, 2001).…”
mentioning
confidence: 99%
“…Note: method based on the procedure of Morales and co-workers (Morales, Corbett & DeGrado, 1998) where it is reported at larger scales. We exemplify here the procedure on a 76 µmol scale, which is routinely carried out in our laboratory.…”
Section: Equipment Setupmentioning
confidence: 99%
“…1,2 Further, the polymer-supported synthesis has also been applied in a variety of organic reactions including the synthesis of natural products, heterocycles and in medicinal chemistry. [3][4][5][6][7][8][9][10] Synthesis of 10-substituted isoalloxazines by the acidic cyclocondensation of 2-substituted aminoanilines with alloxan monohydrate in aqueous and organic solvents has been reported by us. [11][12][13][14][15] Now, we report an improved synthesis of selected novel 10-substituted isoalloxazine-7-carboxylic acids via polymer-support to examine the feasibility of polymer-support synthesis in the synthesis of biologically active isoalloxazines.…”
Section: Introductionmentioning
confidence: 99%